Influences on and patterns in total gaseous mercury (TGM) at Harwell, England. Issue 3 (22nd January 2015) - Kentisbeer, J.; Leeson, S. R.; Clark, T.; Malcolm, H. M.; Cape, J. N.
Abstract : Understanding variation in total gaseous mercury in the southern UK using wind sector and air mass back trajectory analysis to assess a range of influences and sources, local to long-range. Abstract : Total gaseous mercury (TGM) was monitored during 2013 at the rural monitoring site, Harwell, England using the Tekran 2537A monitoring system. Average TGM for the year was 1.45 ± 0.24 ng m −3 . This is comparable to other northern hemisphere studies, but on average 0.5 ng m −3 higher than at its sister monitoring station at Auchencorth Moss, Scotland, but 14% lower than that found in a similar study at the same location of 1.68 ng m −3 in 1995/6. Using wind sector analysis we show the important influence of local emissions, with our data showing that the largest influence on TGM observed is that of the adjacent Science & Innovation campus, making the site more a 'suburban background'. By using co-located measurements of black carbon and sulphur dioxide as tracers, we present an initial investigation into the impact of the closure of Didcot A coal fired power station, which ceased operating in March 2013. Further analysis using air mass back trajectories shows the long-range contribution to TGM from continental Europe, and that the lowest levels are associated with marine air masses from the west.